Analisis Rasio Keuangan Untuk Menilai Kinerja PT. Lancartama Sejati Tbk - Rani Zahra; Aulia Diana Savitri; Elice Violeta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to find out how Financial Ratio Analysis Assesses the Company's Financial Performance and measures the health level of PT. Lancartama Sejati Tbk for the 2017-2019 period is reviewed based on liquidity ratio, solvency ratio, probability ratio and activity ratio. This study employs a qualitative descriptive analysis of data gleaned from PT Lancartama Sejati Tbk's financial statements for the years 2017-2019. This research shows that PT. lancartama Sejati Tbk is performing well financially as measured by the Liquidity ratio with the help of the Current Ratio and the Quick Ratio. The solvency ratio is calculated by dividing the total debt by the total assets. Profit Margin, Return on Equity, and Return on Assets constitute the basis of the profitability ratio. Activity ratios are calculated by the use of the Fixed Asset Turn Over, Asset Turn Over, and Inventory Turnover models.